SOCIAL ENTREPRENEURSHIP IN THE TIME OF COVID-19 - Solichul Hadi Achmad Bakri (President University, 2021)
In the face of a modern global depression like the one we are facing today, where economy is foreseen to be contracting, capital gains wiped out, rise in unemployment, and the welldefined infrastructure network in more developed economies is shaken, it is important to once again go back to the principle of entrepreneurship. As a mean to survive, necessity-based entrepreneurship pushes individuals and businesses into a form of innovation that allows them to create gain in order to support their livelihood. In saying that however, in the time of crisis we are facing like today, a sense of community should also be at the forefront of entrepreneurs’ mind, as it is not only enough to create gain for oneself, but the assistance for the wider community should also be provided. Hence, social entrepreneurship might be key in combating the impact of this economic crisis. This paper will examine how social entrepreneurs, by engaging with each other by forming an alliance or a network could continue to innovate as a means to find opportunities amidst the challenges of the current time. For the purpose of reaching the objective, a combination of both qualitative and quantitative research method is used, in which theories from related journals are studied that would be coupled with the analysis of financial figures collected from the case study. The finding of the research has suggested that social entrepreneurship might be part of the solution in combating the impact of economic crisis that stems from natural disaster, specifically in this case a pandemic of Covid-19.Keywords: social entrepreneurs, network, necessity-based entrepreneurs, economic crisis